Critique and Theory Building: Producing Knowledge “From the Kitchen” - Jacques, Roy (Academy of Management Review, 1992)
Discussion of what constitutes “good” scholarly critique in organisational studies usually emphasises procedural issues. The values guiding critique are seldom discussed. This article characterizes current critical practices as an “ethic of Judgment” and draws from feminist theory to suggest the possibility of critique Informed by an “ethic of care.” The purpose of this comparison is to draw attention to the Important role the values that structure critique play in the development of organisation theory.